The Actual Status of Elderly Orofacial-Function Improvement Program in Seoul and Gyenggi-Area - Do-Seon Lim; Ju-hee Kim; So-yeon Lee; Im-Hee Jung (The Korean Society of Dental Hygiene Science, 2021)
Background: Although the orofacial-function improvement exercise (OFIE; oral exercise) was first introduced in Korea 10 years prior, it is still not covered by medical insurance, and no detailed survey on the dissemination of related programs has been conducted. Therefore, this study investigated the actual status of the education and practice of OFIE among the elderly and at elderly welfare institutions in the Seoul and Gyeonggi Provinces.Methods: Senior citizens aged more than 65 years old, public health centers (total of 69) and elderly welfare institutions (including nursing homes and elderly welfare centers, total of 56) per administrative area in the Seoul and Gyeonggi Provinces were targeted. We analyzed 200 elderly people and 93 institutions who agreed to participate in the survey. For the elderly, general characteristics, experience and route, current practice, and necessity regarding OFIE were investigated. For institutions, the history and plan of education programs on OFIE were investigated. Results: Regardless of the general characteristics, both the rate of experience and practice for OFIE were low overall; moreover, although they felt it was necessary, they had insufficient motivation for its implementation. Moreover, only a few institutions which were operating the education about OFIE regardless of the COVID-19 situation.Conclusion: Although OFIE is necessary for the elderly, its distribution remains insufficient. Therefore, further efforts are needed to expand the education and raise the awareness of oral exercise among elderly individuals and senior welfare institutions.